2017
DOI: 10.1097/aog.0000000000002202
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Order of Successive Office Hysteroscopy and Endometrial Biopsy for the Evaluation of Abnormal Uterine Bleeding

Abstract: ClinicalTrials.gov, NCT02472184.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…A 2018 randomized clinical trial showed that performing a hysteroscopy first ensures a better image, whereas a biopsy yields an adequate tissue sample with fewer attempts [21]. In the current literature, there are no systematic correlation data between the hysteroscopic features of a single hysteroscopic elementary lesion and the diagnosis of endometrial hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2018 randomized clinical trial showed that performing a hysteroscopy first ensures a better image, whereas a biopsy yields an adequate tissue sample with fewer attempts [21]. In the current literature, there are no systematic correlation data between the hysteroscopic features of a single hysteroscopic elementary lesion and the diagnosis of endometrial hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…There is no doubt that hysteroscopy and targeted biopsy represent a diagnostic evolution of blind techniques, such as pipelle, in the identification of focal endometrial pathologies, including those of a hyperplastic type [3,4,27,33]. At present, blind biopsies commonly do not allow any focal lesions to be assessed, but some authors suggest that biopsies under hysteroscopic guidance could be significantly improved by the use of blind sampling, especially when the hyperplastic process is widespread [21].…”
Section: Discussionmentioning
confidence: 99%
“…Random endometrial biopsies are advocated to improve the sensitivity and specificity of the diagnostic method [ Figure 2 ]. [ 35 36 37 ]…”
Section: E Ndometrial S Ampling With H Ysteroscopy Using 5 F R mentioning
confidence: 99%